Kinetics of heat induced muscle protein denaturation of brown shrimp (Crangon crangon). (December 2016) - Verhaeghe, Thomas; Vlaemynck, Geertrui; De Block, Jan; Van Weyenberg, Stephanie; Braeckman, Ruben; Hendrickx, Marc
Abstract: To optimize the quality of cooked brown shrimp ( Crangon crangon ), quantitative data on the influence of all relevant process parameters (treatment time, temperature, NaCl concentration) on several quality attributes are required. Surprisingly, kinetic data and models on heat induced quality changes of brown shrimp are scarce. In this study, the denaturation of muscle proteins was studied by differential scanning calorimetry. The thermal denaturation kinetics of actin, the most heat resistant muscle protein, were determined and showed a first order decay with k 72 °C = 0.038 ± 0.001 min −1 and Ea = 388 ± 7.3 kJ/mol. Spiking experiments showed that NaCl (concentrations in the range from 1 to 5% NaCl) had a negligible influence on the actin thermal stability. The kinetic data obtained can be used to quantitatively evaluate the doneness of cooked shrimp. Highlights: Thermograms of the muscle tissue of brown shrimp were obtained by means of DSC. Thermal denaturation kinetics of actin were determined. Kinetic parameters were estimated using a one-step non-linear regression. Spiking experiments showed a small influence of NaCl concentrations (1–5%). Data shows importance of actin denaturation kinetics at low treatment temperatures (<77.5 °C).